Prevalence and Predisposing Factors of Human Immunodeficiency Virus Infection among the Boda-Boda Riders in Mbarara Municipality-Uganda - Tumwebaze, Mathias; Otiam, Emmanuel O.; Rukindo, Kakwezi Margaret; Mwesigwa, John (Open Journal of Epidemiology, 2020)
Boda-Boda is a well-known and booming motorcycle taxi that employs youths to earn a living. They transport passengers at a faster rate where other means of transport are inaccessible or would be time consuming. Global statistics show that HIV has continued to be a major global Public Health issue especially among the “Most At-risk Populations” (MAPs) that include commecial transporters and Boda-Boda riders. Aim: This study aimed at assessing the prevalence and predisposing factors for HIV/AIDS among Boda-Boda riders living in Mbarara Municipality. Specifically, the study determined the prevalence of HIV among the Boda-Boda riders, identified social demographic predisposing factors for HIV and determined knowledge of Boda riders on prevention of HIV. Study setting: Boda-Boda operators in the transport sector are at high risk of HIV infection but the HIV status of the Boda Riders in Mbarara was not known a reason why the study was instituted: Study design: This was an analytical and descriptive cross-sectional study that employed quantitative methods of data collection. The study population comprised the registered Boda-Boda operators from two divisions of Kakoba and Kakiika in Mbarara municipality. Sample size and sampling methods: Using Morgan’s table (1970), the population of the registered Boda Riders was 15,041; this corresponded to a sample size of 375 respondents by Morgan Table. Systematic sampling procedure was used to get every 3rd registered rider on the list. Data collection: A pre-tested structured tool aided data collection after group pretest counseling. Individual counseling was also done prior to testing and giving results. The laboratory technologists drew blood to determine the sero-status of the respondents. Results were recorded as tested reactive (TRR) or tested non-reactive (TR). Unigold was used as tie breaker to confirm their diagnosis in order to ascertain those who were HIV positive on determine. Data analysis: Analysis was done at univariate, bivariate and multivariate using STATA version 13, Statistical significance of the relationship was determined for the p-value (p ≤ 0.05). Significant variables were then considered at multivariate level of analysis. Results: More than half 195 (52%) of the Boda-Boda cyclist had attained primary level of education and 36.5% secondary education. HIV prevalence among Boda-Boda riders was 9.9%. Riders who had never heard of VCT/HCT screening for HIV were three times likely to acquire HIV compared to those who ever heard of VCT/HCT screening (OR = 3.35; 95% CI 1.14 9.83; p = 0.027). Those with multiple partners were six times more likely to acquire HIV/AIDS compared to those who buy sex from prostitutes (OR = 6.13; 95% CI 1.54 24.38; p = 0.01). The level of awareness of VCT was found high at (94.7%), and the gen general knowledge about utilization and importance of VCT services was at 80%, however condom use as a preventive measure was found low at 44.3% among the respondent Boda-Boda riders. Conclusion: Boda-Boda riders had high HIV prevalence of 9.9% compared to that of Mbarara district at 6.1% and much higher than 5.7% national HIV prevalence level. The predisposing factors to acquire HIV/AIDS were having multiple sexual partners, not having heard of HIV counseling and testing as well as low and inconsistent condom use at 44.3%. The study recommends health service providers and HIV counselors to intensify awareness and behavior change campaigns on condom use among the Boda-Boda riders as preventive measure against HIV.
Keywords: Boda-Boda Riders, HIV Prevalence in Boda-Boda, VCT/HCT Screening for HIV, Condom Use